Postmortem microbiology sampling following death in hospital: an ESGFOR task force consensus statement. Issue 5 (19th January 2019) - Burton, Julian L; Saegeman, Veroniek; Arribi, Ana; Rello, Jordi; Andreoletti, Laurent; Cohen, Marta C; Fernandez-Rodriguez, Amparo
Abstract : Postmortem microbiology (PMM) is a valuable tool in the identification of the cause of death and of factors contributory to death where death has been caused by infection. The value of PMM is dependent on careful autopsy planning, appropriate sampling, minimisation of postmortem bacterial translocation and avoidance of sample contamination. Interpretation of PMM results requires careful consideration in light of the clinical history, macroscopic findings and the histological appearances of the tissues. This consensus statement aims to highlight the importance of PMM in the hospital setting and to give microbiological and pathological advice on sampling in deaths occurring in hospital.